Religion and class in America : culture, history, and politics - McCloud, Sean.; Mirola, William A. (International Studies in Religion and Society, 2009)
Class has always played a role in American religion. Class differences in religious life are inevitably felt by both those in the pews and those on the outside looking inches This volume starts a long overdue discussion about how class continues to matter - and perhaps even ways in which it does not - in American religion. Class is indeed important, whether one examines it through analysis of events and documents, surveys and interviews, or participant observation of religious groups. The chapters herein examine class as a reality that is both material and symbolic, individual and corporate. Religion and Class in America examines the myriad ways in which class continues to interact with the theologies, practices, beliefs, and group affiliations of American religion.